Medical Higher Education Institutions in Medicine and Science Lessons from the Use of Information Technology in the Organization of the Laboratory of Multimedia Tools - Ismatullayevich, Nematov Nizom (American Journal of Biomedicine and Pharmacy, 2024)
the laboratory of information technologies in higher education institutions on the subject of the use of multimedia tools in the organization of the lessons, plays an important role in increasing the efficiency of the educational process. In this article, the importance of multimedia tools in education, will affect the coverage of indications and the quality of their education. As noted, the materials provided by interactive multimedia tools, students to understand the subject more deeply and practical skills that will help you to improve. Also, the use of the article in multimedia tools and modern methods in the process of their education in higher education is given more information about the role. As a result, the use of multimedia tools and promising directions in this area have a positive impact on the quality of education will be discussed.